2015
DOI: 10.1007/s11064-015-1662-6
|View full text |Cite
|
Sign up to set email alerts
|

Antiamnesic and Antioxidants Effects of Ferulago angulata Essential Oil Against Scopolamine-Induced Memory Impairment in Laboratory Rats

Abstract: Ferulago angulata (Apiaceae) is a shrub indigenous to western Iran, Turkey and Iraq. In traditional medicine, F. angulata is recommended for treating digestive pains, hemorrhoids, snake bite, ulcers and as sedative. In the present study, the effects of inhaled F. angulata essential oil (1 and 3%, daily, for 21 days) on spatial memory performance were assessed in scopolamine-treated rats. Scopolamine-induced memory impairments were observed, as measured by the Y-maze and radial arm-maze tasks. Decreased activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
6
23
0
Order By: Relevance
“…Also, F. angulata extract attenuates oxidative stress in brain tissue in a rat model of Parkinson's disease (40). Essential oil of F. angulata has cognition-enhancing effect and improves scopolamine-induced memory impairment and oxidative stress (41). In the present study, F. angulata extract significantly ameliorated Aβ-induced neuronal cell death and attenuated Aβ-induced ROS production and oxidative stress.…”
Section: Discussionsupporting
confidence: 64%
“…Also, F. angulata extract attenuates oxidative stress in brain tissue in a rat model of Parkinson's disease (40). Essential oil of F. angulata has cognition-enhancing effect and improves scopolamine-induced memory impairment and oxidative stress (41). In the present study, F. angulata extract significantly ameliorated Aβ-induced neuronal cell death and attenuated Aβ-induced ROS production and oxidative stress.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, 10 days pretreatment of animals with D. integrifolia significantly counteracted the reduction of the percentage of spontaneous alternation induced by scopolamine suggesting significant improvement of space related short – term memory by the decoction of D. integrifolia ( Hritcu et al, 2012 , 2015 ; Beppe et al, 2014 ). The effect of D. integrifolia and that of tacrine a cholinesterase inhibitor used in the treatment of AD were comparables.…”
Section: Discussionsupporting
confidence: 59%
“…Our results with the MWM suggest that D. integrifolia improves spatial long-term memory ( Cheng et al, 2011 ). The results of MWM confirmed that pretreatment with D. integrifolia counteracted scopolamine induced learning and memory deficit thus D. integrifolia is neuroprotective ( Konar et al, 2011 ; Hritcu et al, 2015 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For instance, different extracts and coumarins of the plant exerted moderate antiradical scavenging, antibacterial, and antioxidant activities . Moreover, in the literature antioxidant activity, in vivo anxiolytic and antidepressant for the EO, along with cytotoxicity, apoptosis‐inducing, and in vitro anticancer effects of the extracts were reported. Furthermore, the AcOEt and methanolic extract of F. angulata previously revealed the highest levels of phenolic compounds among its various extracts…”
Section: Introductionmentioning
confidence: 99%